What does it mean to be a man? Trans masculinities, bodily practices, and reflexive embodiment - Aboim, S.; Vasconcelos, P. (Men and Masculinities, 2022)
Confronted with the centrality of the body for trans-masculine individuals interviewed in the United Kingdom and Portugal, we explore how bodily-reflexive practices are central for doing masculinity. Following Connell’s early insight that bodies needed to come back to the political and sociological agendas, we propose that bodily-reflexive practice is a concept suited to account for the production of trans-masculinities. Although multiple, the journeys of trans-masculine individuals demonstrate how bodily experiences shape and redefine masculinities in ways that illuminate the nexus between bodies, embodiments, and discursive enactments of masculinity. Rather than oppositions between bodily conformity to and transgression of the norms of hegemonic masculinity, often encountered in idealizations of the medicalized transsexual against the genderqueer rebel, lived bodily experiences shape masculinities beyond linear oppositions. Tensions between natural and technological, material and discursive, or feminine and masculine were keys for understanding trans-masculine narratives about the body, embodiment, and identity.